Cardiotoxicity Complication of Radiotherapy - Wisman, Beta Agustia; Nasution, Sally Aman; Panggabean, Marulam M (Jurnal Penyakit Dalam Indonesia, 2017)
Radiation is an important modality in the management of malignancy. Some cases of malignancy requiring radiotherapy in the chest include breast cancer, Hodgkin's lymphoma, or lung cancer.Cardiotoxicity due to radiotherapy can occur within 3 to 29 years after radiotherapy, mostly in the second or third decade after therapy. Some cardiovascular complications resulting from radiotherapy may affect pericardial, myocardial, vascular, heart valves and conduction disturbances. Symptomatic cardiotoxicity may occurs 10% in patients undergoing radiotherapy in the chest area. It is important for clinicians to understand the cardiotoxicity of radiotherapy for educational purposes, therapeutic and dosing considerations, treatment monitoring and early detection. Early detection and post-radiation monitoring have an important role to reduce morbidity and mortality due to cardiovascular disease after radiotherapy and comprehensive management is necessary